2018
DOI: 10.1002/pon.4934
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and psychological distress in cancer survivors: The role of psycho‐social resources for resilience

Abstract: Objective: To examine the association between scores on the Protective Factors for Resilience Scale (PFRS) (as a measure of a person's psycho-social resources for resilience) and quality of life as well as symptoms of psychological distress for adult cancer survivors. Methods:In this cross-sectional study, 295 cancer survivors (59% female) provided background demographic information and completed the PFRS as well as measures of quality of life and psychological distress previously validated with cancer survivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
58
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 36 publications
(48 reference statements)
1
58
1
3
Order By: Relevance
“…Breast cancer (BC) is the most prevalent cancer in women in the Western world [1]. Although the prognosis has dramatically improved, BC still causes considerable physical and psychological consequences for many women [2][3][4][5][6]. Receiving a BC diagnosis means emotional turmoil for the patient, although the reactions may differ due to, e.g., the personal stability of the individual [2].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Breast cancer (BC) is the most prevalent cancer in women in the Western world [1]. Although the prognosis has dramatically improved, BC still causes considerable physical and psychological consequences for many women [2][3][4][5][6]. Receiving a BC diagnosis means emotional turmoil for the patient, although the reactions may differ due to, e.g., the personal stability of the individual [2].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that BC has a major impact on women's health-related quality of life (HRQoL) when measured by valid instruments, e.g., the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC-QLQ), the Functional Assessment of Cancer Therapy Breast Cancer (FACT-B) and the Short Form Health Survey (SF-36) [3]. As the incidence of BC increases and survivors live longer, HRQoL has become an increasingly important outcome measure for BC patients [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations